PENGANGKATAN DAN PEMBERHENTIAN KAPOLRI OLEH PRESIDEN - Rizky Putra Zulkarnain (Yuridika, 2015)
The 1945 Constitution of Indonesia  as the constitutional authority of the President shall arrange everything as the highest authority of the executive. Such arrangements must be made clear boundaries so that later the president does not exceed its authority itself and cause a totalitarian power . Prerogative is one authority regulated implicitly by the constitution and gave full power to the President to implement this right , such as the appointment and dismissal of the Chief of Police.